Implementing beyond budgeting : the case of 1912 ehf. - Erna Sigurðardóttir 1987- (2018)
The annual budgeting process is the most dominant control system among organizations but it has gained much criticism in recent years. 1912 ehf. is one of few companies in Iceland that has started their journey in implementing Beyond budgeting, an alternative management model that helps organizations to improve the annual budgeting process. Beyond Budgeting is however more than a new tool for the financial department to improve the budgeting process. Beyond Budgeting is about a change in corporate culture and employee´s behaviour and attitude. It is therefore important, when an organization decides to implement a management model like this to focus on how the change is presented to the employees. This dissertation covers the implementation of the Beyond Budgeting model within the company 1912 ehf. The main purpose of this dissertations was to analyse how an Icelandic company is implementing the Beyond Budgeting model and what impact the implementing process has on the employees. The method applied in this research was a case study. One-on-one interviews were conducted in person with 11 employees at 1912 ehf. A guiding set of questions was used for the interviews. The results indicated that 1912 ehf. had come a long way in the philosophy behind Beyond Budgeting before they formally decided to implement the model and the implementation was fast and no emphasis was placed on systematically implementing all the 12 principals of Beyond Budgeting. The greatest emphasis was on the implementation of a rolling forecast. Based on the data collected it appears that employees are happy with the changes and see the benefits of using the model. They do not experience more stress and it can be estimated from the results that gaming behaviour is to a lesser extent existing among employees. However, there is a clear difference between employees who were part of the executive team and the product managers regarding the understanding of the model and how relevant they thought it was for their work. Keywords: Human Resource ...